Program Literasi Berbasis Permainan Siaga Petra untuk Menumbuhkan Sikap Empati Siswa - Ayudiah Anggraini (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to foster an empathetic attitude in grade 1b students in Elementary School of 2 Rejang Lebong through the literacy program based Siaga Petra game. The research method used is Classroom Action Research which is carried out in 3 cycles. The research subjects were students of class 1b Elementary School of 2 Rejang Lebong, totaling 29 people consisting of 15 boys and 14 girls. The instrument of this research is the observation journal of empathy attitude. Empathy observation journal data were analyzed descriptively from the number of occurrences of indicators The results of the research in cycle 1 there are 6 indicators of empathy that appear. Cycle 2 there are 9 indicators of empathy that appear. Cycle 3 there are 9 indicators of empathy that appear. Based on the results of this study, it can be concluded that the application of the literacy program based Siaga Petra game can foster student empathy.